ASSESSMENT OF DEBT CAPACITY OF INDUSTRIAL ENTERPRISES - Victor V. Prokhorov (Статистика и экономика, 2016)
The article considers the task associated with the assessment of debt capacity of industrial enterprises,help enterprises to identify to the maximum extent ofthe planned bond issue. Focuses on the study of themethods of debt capacity of industrial enterprises. Weconsider the problem of developing a method of assessing debt capacity of industrial enterprises, whichallows to jointly consider the total assets and cash ﬂows of the company. A method for estimating debt capacity based on joint account total assets and cash ﬂ ows of the company. The proposed method uses estimates of existing assets and cash ﬂows of an industrial enterprise. The results obtained suggest the possibility of applying the proposed method for estimating debtcapacity of industrial enterprises in the Russian context.The results may be applicable Russian industrial enterprises organizing issue public bonds, and investmentcompanies prominent organizers of corporate bondsand other organizations specializing in investments inthe Russian public corporate bonds.